Analysis of Maqashid Al-Syari'ah in Supporting the Family By Begging in Panyabungan Mandailing Natal District - Raja Ritonga; Khairani Rangkuti (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
Fulfilling family maintenance is an obligation for a head of family. In fulfilling this living, it must be carried out with full responsibility and prioritizing halal and thoyyib. However, some fulfill the needs of their family by begging in a certain mode. The purpose of this research is to explain the maqashid al-shariah analysis of fulfilling family income by begging. This research is a field study in Panyabungan, Mandailing Natal. In collecting data, researchers conducted observations, interviews and documentation. Furthermore, the data findings were analyzed descriptively with maqashid al-shari'ah. As a result of the findings, beggars who do their job to provide for their families are grouped into three types, namely (1) begging with physical and mental disabilities, (2) begging by pretending to be disabled, (3) begging involving other family members. In the maqasid al-shariah analysis, it is permissible that people beg because they are mentally or physically disabled and do not have anyone else to support themselves and their families. Meanwhile, begging by pretending and involving other families is not justified, because it eliminates self-dignity and dignity.